G09 Structural connectivity-based topography of the basal ganglia is altered in premanifest and early manifest Huntington's disease. (29th August 2012) - Novak, M; Seunarine, K; Gibbard, C; Clark, C; Tabrizi, SJ
Abstract : Background: HD is associated with anatomically extensive degeneration of white matter, indicated by widespread loss of volume and altered diffusion qualities. Degeneration of selected white matter tracts has previously been demonstrated, showing that white matter degeneration results in altered structural connectivity in specific pathways. We hypothesised that disease-associated changes in structural connectivity are inter-connected; we therefore used multivariate analyses to characterise disease-associated patterns of altered connectivity across all structural connections between the basal ganglia and the cerebral cortex. Aims: (a) To characterise disease-associated patterns of structural connectivity as described above; (b) to use voxel-based techniques to define these patterns with unprecedented anatomical precision; and (c) to define associations between connectivity patterns and genetic load and clinical symptoms. Methods: Probabilistic tractography was used to define the structural connections between every (seed) voxel in the basal ganglia and 54 cortical (target) regions for 14 early manifest and 17 premanifest HD gene carriers and 14 controls from the Track-HD London cohort. Each basal ganglia voxel was assigned a voxel connectivity pattern; this represented the cortical region(s) to which that voxel was connected. Group-average voxel connectivity maps were created to illustrate altered topographic organisation in the HD subjects in comparison with controls. Singular value decomposition and canonical variance analysis were used for statistical analyses. Results: Topographic organisation of the basal ganglia was altered in premanifest and early manifest HD gene carriers in comparison with controls. There was no difference between the connectivity patterns of premanifest and manifest HD gene carriers. Clinical scores, including total motor score, and genetic load were associated with specific connectivity patterns. Conclusions: Topographic organisation of the basal ganglia is altered in HD. Connectivity patterns are similar in premanifest and manifest HD, which may suggest congenital or early onset static (or slowly changing) disease-associated changes. Altered connectivity patterns are linked to clinical phenotype and thus have functional relevance.